Modulation of ERK1/2 and p38 MAPK signaling pathway by ATP in osteoblasts: involvement of mechanical stress-activated calcium influx, PKC and Src activation - Katz, Sebastian (2006)
There is evidence that extracellular nucleotides, acting through multiple P2 receptors, may play an important role in the regulation of bone metabolism by activating intracellular signaling cascades. We have studied the modulation of mitogen-activated protein kinase (MAPK) signaling pathways and its relationship to changes in intracellular calcium concentration ([Ca2+]i) induced by ATP in ROS-A 17/2.8 osteoblastic cells. ATP and UTP (10 μM) increased [Ca2+]i by cation release from intracellular stores. We have found that when the cells are subsequently subjected to mechanical stress (medium perturbation), a transient calcium influx occurs. This mechanical stress-activated calcium influx (MSACI) was not observed after ADP stimulation, indicating that P2Y2 receptor activation is required for MSACI. In addition, ERK 1/2 and p38 MAPK were activated by ATP in a dose- and time-dependent manner. This activation was almost completely blocked using neomycin (2.5 mM), an inhibitor of phosphoinositide-phospholipase C (PI-PLC), Ro 318220 (1 μM), a protein kinase C (PKC) inhibitor, and PP1 (50 μM), a potent and selective inhibitor of the Src-family tyrosine kinases. Ca2+-free extracellular medium (containing 0.5 mM EGTA) and the use of gadolinium (5 μM), which suppressed MSACI, prevented ERK 1/2 and p38 phosphorylation by ATP. Altogether, these results represent the first evidence to date suggesting that P2Y2 receptor stimulation by ATP in osteoblasts sensitizes mechanical stress activated calcium channels leading to calcium influx and a fast activation of the ERK 1/2 and p38 MAPK pathways. This effect also involves upstream mediators such as PI-PLC, PKC and Src family kinases.